Work education for the educable mentally retarded in the primary level - Fernandez, Rebecca D.; Mendonez, Belen C.; Balena Magdalena C. (Quezon City College of Education, University of the Philippines Diliman, 1970)
The aim of the study is to determine the activities and experiences that should be included in an effective work education program for the educable mentally retarded in the primary level. Specifically, it seeks to identify the objectives in work education for the educabale mentally retarded at the primary level, areas of work education that should be included in the curriculum for the mentally retarded in the primary level, the expected outcomes of an effective work education program for these children, and some principles to remember in teaching work education to the educable mentally retarded in the primary level.
Vita.
Thesis (Master of Arts in Teaching : Special Education-Mentally Retarded)--University of the Philippines, Diliman.
Keywords: Children with mental disabilities -- Education (Primary) -- Philippines; Special education -- Philippines; Vocational education -- Philippines